Conflicts of belonging: the border rural clusters located between the municipalities of Apodi and Severiano Melo (RN) (PerCursos, 2025)
In some rural clusters located in the internal border area between the municipalities of Apodi and Severiano Melo, in the state of Rio Grande do Norte, there are situations of territorial conflicts, caused by a reconfiguration of the boundaries between the two municipalities. This raises the following question: What are the impacts of the reconfiguration of territorial boundaries in rural clusters located in the internal border between the municipalities of Apodi and Severiano Melo (RN)? The work was carried out through a literature review based on approaches that can contribute to the focus of the study, as well as research on secondary data, and a field visit. In this regard, the objective is to identify the impacts of the reconfiguration of territorial boundaries in rural border clusters. Among the results, conflicts of a legal-administrative nature were observed, which impact public planning and management, especially in the provision and quality of public services, and territorial identity, related to the feeling of municipal belonging.
Keywords: territory; territorial identity; conflicts; border rural agglomerations